(untitled) (Prostor, 2024)
The integration of environmental aspects in land use plans (LUPs) through SEA varies across Europe and their efficiency is still not well known, motivating the research of SEA implementation for LUPs. The main aim of the research is to evaluate the methods of integrating environmental aspects into LUPs, based on ten best practices, five from Slovenia and five from other EU Member States. The research methodology proceeds from the review of various literature and studies, on the basis of which we have developed fifty efficiency criteria and evaluated the methods used in the LUP for each step of the SEA: (I) scoping, (II) environmental report preparation, (III) consultations with ministries and public organizations responsible for specific environmental issues, (IV) public participation, (V) decision-making and (VI) monitoring. The research has shown that the methods used differ in scoping, consultations, public participation, and monitoring. We have identified the methods that are most effective in each SEA step. The research findings emphasise the importance of scoping and monitoring methods. The conclusion suggests further research of efficiency by questionnaire.